Combating Modern Slavery: The Strategy of Indonesian Government to Protect Migrant Workers (Department of International Relations, Universitas Brawijaya, 2021)
Economic migration create opportunities as well as humanitarian challenge. People travel across national boundary looking for work in the country destination. They would benefit their hosted as well as sending high amount of remittance for home. However, those dream were not applicable to all economic migrant when some of them fall victim into human trafficking. This research would investigate the strategy as well as challenges by Indonesia government and NGOs to promote protection of Indonesian migrant worker. It is imperative to evaluate state policies, state diplomacy, transnational advocacy network, and the nature of companies as agent of service provider. It would show how current practices and law has loopholes that create challenges for public private partnership to provide adequate support for Indonesian migrant worker. Investigation is conducted through interview, observation and literature review. The struggle to end modern slavery shall be one among priority in protecting civilian abroad, if the government is serious to minimize economic inequality and to change itself into welfare nation.